GE_GERICHTE P/6722/2024 vom 19. August 2025 - GE Cour de justice (2025)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;ESCROQUERIE;ABUS DE CONFIANCE;CONTRAINTE(DROIT PÉNAL) | CPP.310; CP.146; CP.138; CP.181; CP.251